Perinuclear Anti-Neutrophil Cytoplasmic Antibodies (pANCA) Impair Neutrophil Candidacidal Activity and Are Increased in the Cellular Fraction of Vaginal Samples from Women with Vulvovaginal Candidiasis - Ardizzoni, Andrea; Sala, Arianna; Colombari, Bruna; Giva, Lavinia Beatrice; Cermelli, Claudio; Peppoloni, Samuele; Vecchiarelli, Anna; Roselletti, Elena; Blasi, Elisabetta; Wheeler, Robert T.; Pericolini, Eva (Journal of fungi (Basel), 2020)
Vulvovaginal candidiasis (VVC) is primarily caused by Candida albicans and affects 75% of childbearing age women. Although C. albicans can colonize asymptomatically, disease is associated with an increased Candida burden, a loss of epithelial tolerance and a breakdown in vaginal microbiota homeostasis. VVC symptoms have been ascribed to a powerful inflammatory response associated with the infiltration of non-protective neutrophils (PMN). Here, we compared the immunological characteristics of vaginal fluids and cellular protein extracts obtained from 28 VVC women and from 23 healthy women colonized by Candida spp. We measured the levels of antibodies against fungal antigens and human autoantigens (anti-Saccharomyces cerevisiae antibodies (ASCA), C. albicans germ tube antibodies (CAGTAs) and perinuclear anti-neutrophil cytoplasmic antibodies (pANCA)), in addition to other immunological markers. Our results show that the pANCA levels detected in the cellular protein extracts from the vaginal fluids of symptomatic women were significantly higher than those obtained from healthy colonized women. Consistent with a potential physiologically relevant role for this pANCA, we found that specific anti-myeloperoxidase antibodies could completely neutralize the ex vivo killing capacity of polymorphonuclear cells. Collectively, this preliminary study suggests for the first time that pANCA are found in the pathogenic vaginal environment and can promptly impair neutrophil function against Candida, potentially preventing a protective response.